2022
DOI: 10.1002/cpz1.423
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cell–Based in vitro Model for Neurotoxicity Testing

Abstract: Neurotoxicity (NT) testing for regulatory purposes is based on in vivo animal testing. There is general consensus, however, about the need for the development of alternative methodologies to allow researchers to more rapidly and cost effectively screen large numbers of chemicals for their potential to cause NT, or to investigate their mode of action. In vitro assays are considered an important source of information for making regulatory decisions, and human cell-based systems are recommended as one of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 123 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…Moreover, M2-EVs may have some additional advantages, such as rich source, regulatory potential, and tropism effect, compared to commonly used MSC-EVs. To acquire large numbers of cells for EV production, in vitro long-term culture and expansion of MSCs are needed, which is costly and time-consuming (~1–2 months) and may also induce MSC senescence [ 51 ]. A large number of M2-PMφ (~10 million in 1 bag (~2 L) human dialysate) can be readily collected from multiple patients with peritoneal dialysis [ 17 ], which might become a rich source for EV production in the shorter term (~3–7 days in our study).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, M2-EVs may have some additional advantages, such as rich source, regulatory potential, and tropism effect, compared to commonly used MSC-EVs. To acquire large numbers of cells for EV production, in vitro long-term culture and expansion of MSCs are needed, which is costly and time-consuming (~1–2 months) and may also induce MSC senescence [ 51 ]. A large number of M2-PMφ (~10 million in 1 bag (~2 L) human dialysate) can be readily collected from multiple patients with peritoneal dialysis [ 17 ], which might become a rich source for EV production in the shorter term (~3–7 days in our study).…”
Section: Resultsmentioning
confidence: 99%
“…The medium was changed every 48 h, and the cells were cultured up to a maximum of 8 days (fully differentiated stage). Neuronal‐like phenotype characterization was performed by morphological analysis (i.e., evidence of the conversion from the mesenchymal‐ to neuron‐like‐morphology with retractile cell bodies and long branching processes—dendrites and axons), presence of Nissl body (by staining of the granular structures of rough endoplasmic reticulum), and the expression of several neuronal‐specific proteins/markers (by immunofluorescence) such as β‐Tubulin III (a microtubule element of the tubulin family, structural marker predominantly in neurons), microtubule‐associated protein 2 (a mature neuron marker), and enolase (cytoplasmic protein expressed by mature neurons), synaptophysin (indicator of the synapses density), growth‐associated protein 43 (a key factor for axonal growth and elongation), and post‐synaptic density 95 (an important scaffold protein on the post‐synaptic membrane, which plays an important role in the process of synapse formation) (Coccini et al, 2022; De Simone et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…One type of SCs includes the "mesenchymal stem cells" (MSCs), multipotent SCs that exhibit numerous advantages, including the fact that they can be obtained in high yield from healthy human adult tissues, have the advantage over primary and immortalized cells of being capable of continuous, repeated self-renewal, and of forming large populations of stably differentiated cells representative of different tissues of human origin, including cerebral cells (e.g., neuronal and glial cells; Kim et al, 2019;Singh & Kashyap, 2016;Suma & Mohanan, 2015;Zakrzewski et al, 2019) and can be cultured with a minimal laboratory setup and without genetic manipulations. They can be easily obtained from the human umbilical cord with painless, noninvasive, and ethically acceptable collection procedure and be efficiently differentiated in vitro into cells of nonmesodermal origin, including hNLCs (Coccini et al, 2022;Cortés-Medina et al, 2019;Czarnecka et al, 2017;Hernández et al, 2020;Kil et al, 2016;Shahbazi et al, 2016;Shi et al, 2018), which can be used as a powerful tool for chemical neurotoxicological risk assessment in humans (Buzanska et al, 2009;Coccini et al, 2020;De Simone et al, 2020;Kashyap et al, 2015;Singh & Kashyap, 2016;Zychowicz et al, 2014). These hNLCs, serving as a source of "healthy" cells (that are not immortalized or cancer-derived cell lines), species-specific, human based, have been employed to evaluate MG toxicity using a range of concentrations typically detected in the plasma of pathological subjects (Beeri et al, 2011;Haddad et al, 2019;Srikanth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The hucMSCs exhibit a faster renewal rate, stronger proliferation potential, and stronger immunosuppressive ability compared to adult mesenchymal stem cells derived from other mature tissues ( Xu et al, 2018 ; Zha et al, 2021 ). Harvesting the umbilical cord cells is non-invasive and painless and has a wide range of sources without any ethical controversy ( Coccini et al, 2022 ). Moreover, studies have reported that hucMSCs have the potential to cross the blood–brain barrier (BBB) ( Sun et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%